OPPORTUNITIES FOR APPLYING THE EXPERIENCE OF FOREIGN COMPANIES IN REDUCING EMPLOYEE TURNOVER IN THE LABOR MARKET OF UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines the problem of employee turnover in organizations and ways to reduce it. The study is based on a company operating in the labor market of Uzbekistan and analyzes employee turnover data for the period 2022–2024. The analysis shows that the main reasons for employees leaving are low motivation, weak adaptation of new staff, and working conditions.The article evaluates retention measures such as mentoring, financial and non-financial incentives, and onboarding programs for new employees. After these measures were introduced, the level of employee turnover in the company decreased significantly. In addition, the experience of foreign companies is reviewed, and the possibilities of applying some of their practices in Uzbekistan are discussed. The results confirm that a systematic HR approach is important for reducing employee turnover.
Keywords: employee turnover; employee retention; HR strategies; motivation